Augmenting mesenchymal stem cell therapy for osteoarthritis via inflammatory priming: a comparative study on mesenchymal stem cells derived from various perinatal tissue sources - Xia, Xinzi; Sui, Yue; Zhou, Jiawen; Li, Shanshan; Ma, Xiang; Jiang, Jiang; Yan, Yaping (Frontiers in Cell and Developmental Biology, 2023)
Background：Osteoarthritis (OA), a degenerative disease prevalent among the elderly, poses significant challenges due to its high incidence and disability rates. Regrettably, there exists a lack of effective regenerative therapies for the irreversible degradation of cartilage in OA.Mesenchymal stem cells (MSCs), known for their robust differentiation and immune regulatory capabilities, have emerged as promising candidates for OA treatment. MSCs sourced from perinatal tissues offer the dual advantage of convenience in extraction and ethical non-controversy. However, the heterogeneous nature of MSCs derived from different perinatal tissue sources gives rise to varying therapeutic indications. Moreover, the immune response of MSCs may be modulated under the influence of inflammatory factors.In this study, we isolated mesenchymal stem cells from distinct parts of human perinatal tissue: umbilical cord-derived MSCs (UC-MSCs), fetal placenta-derived MSCs (FP-MSCs), and umbilical cord placental junction-derived MSCs (CPJ-MSCs). These cells were cultured in vitro and subjected to a 24-hour treatment with the inflammatory mediator Interleukin-1β (IL-1β). Subsequently, the MSCs were evaluated for changes in proliferation, migration, and regulatory capabilities. To assess the comparative anti-injury potential of MSCs from different sources, primary articular chondrocytes (ACs) were exposed to H2O2-induced injury and co-cultured with IL-1β-primed MSCs. Changes in the proliferation, migration, and regulatory abilities of ACs resembling those observed in OA were examined.Results：Following IL-1β treatment, all three types of MSCs displayed decreased rates of proliferation and migration. Notably, their chondrogenic differentiation capacities exhibited an enhancement. Additionally, diverse MSCs exhibited a degree of efficacy in restoring damaged ACs in vitro. Among these, CPJ-MSCs demonstrated superior potential in promoting cartilage cell proliferation, while FP-MSCs displayed notable anti-inflammatory effects.Conclusion： Our findings underscore the substantial capacity of primed FP-MSCs and CPJ-MSCs to alleviate the injury in OA-like ACs. Consequently, this study advocates for the prospective use of preconditioning strategies involving FP-MSCs and CPJ-MSCs in forthcoming OA therapies.